Age-Related Psychophysiological Vulnerability to Phenylalanine in Phenylketonuria - Leuzzi, Vincenzo; Mannarelli, Daniela; Manti, Filippo; Pauletti, Caterina; Locuratolo, Nicoletta; Carducci, Carla; Carducci, Claudia; Vanacore, Nicola; Fattapposta, Francesco (Frontiers in Pediatrics, 2014)
Background. Phenylketonuria (PKU) is caused by the inherited defect of the phenylalanine hydroxylase enzyme, which converts phenylalanine (Phe) into tyrosine (Tyr). Neonatal screening programs and early treatment have radically changed the natural history of PKU. Nevertheless, an increased risk of neurocognitive and psychiatric problems in adulthood remains a challenging aspect of the disease. In order to assess the vulnerability of complex skills to Phe, we explored: a) the effect of a rapid increase in blood Phe levels on event-related potentials (ERP) in PKU subjects during their second decade of life; b) the association (if existing) between psychophysiological and neurocognitive features. Methods. Seventeen early-treated PKU subjects, aged 10 to 20, underwent ERP (Mismatch Negativity, auditory P300, Contingent Negative Variation (CNV), and Intensity Dependence of Auditory Evoked Potentials) recording before and 2 hours after an oral loading of Phe. Neurocognitive functioning, historical and concurrent biochemical values of blood Phe, Tyr, and Phe/Tyr ratio, were all included in the statistical analysis. Results. ERP components were normally detected in all the subjects. In subjects younger than 13 CNV amplitude, W2-CNV area, P3b latency, and Reaction Times in motor responses were negatively influenced by Phe loading. Independently from the psychophysiological vulnerability, some neurocognitive skills were more impaired in younger patients. No correlation was found between biochemical alterations and neurocognitive and psychophysiological findings. Conclusion. The vulnerability of the emerging neurocognitive functions to Phe suggests a strict metabolic control in adolescents affected by PKU and a neurodevelopmental approach in the study of neurocognitive outcome in PKU.